2016
DOI: 10.4322/rbcv.2016.026
|View full text |Cite
|
Sign up to set email alerts
|

Doenças de notificação compulsória em animais de produção no período de 2011 a 2014 no estado do Maranhão

Abstract: ResumoO objetivo do estudo foi realizar levantamento das doenças de notificação compulsória (DNC's) em animais de produção ocorridas no período de 2011 a 2014 no Estado do Maranhão, utilizando os condensados estaduais dos informes mensais, formulário de investigação de doenças inicial (FORM-INs) AbstractThe aim of the study was conducted survey of notifiable diseases (DNC's) in farm animals occurred in the period from 2011 to 2014 in the state of Maranhão, using state condensates of monthly reports, initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
1
3
0
2
Order By: Relevance
“…Although, Pará and Maranhão are neighboring states, the techniques used may have been the main difference between the results, since the technique performed in Pará was ELISAi, a technique with greater sensitivity than the CFT. However, the results from our retrospective study are similar to those from a survey carried out in the Maranhão lowlands (Baixada Maranhense), in which the CFT showed that 0.48% of the horses were positive (CHAVES et al, 2016).…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Although, Pará and Maranhão are neighboring states, the techniques used may have been the main difference between the results, since the technique performed in Pará was ELISAi, a technique with greater sensitivity than the CFT. However, the results from our retrospective study are similar to those from a survey carried out in the Maranhão lowlands (Baixada Maranhense), in which the CFT showed that 0.48% of the horses were positive (CHAVES et al, 2016).…”
supporting
confidence: 87%
“…It is characterized by chronic and acute stages, and leads to notable economic losses, with sociocultural importance. Although, the first records on glanders disease in Brazil dated from the beginning of the 19 th century, through importation of equids from Europe, cases are now being detected again, as seen in the state of Maranhão (KORTEPETER et al, 2001;VAN ZANDT et al, 2013;CHAVES et al, 2016). These infectious and contagious conditions are caused by Burkholderia mallei, a facultative intracellular…”
mentioning
confidence: 99%
“…Another disease that was included in the list of differential diagnoses was glanders. It is a reemerging disease in the country with outbreaks in several states in the Northeast and Southeast (Chaves et al, 2016). According to Ramos et al (2021), between 2010 and 2019, 69 cases of glanders were diagnosed in the state of Rio Grande do Norte, making this disease one of the differential diagnoses of diseases of the respiratory system.…”
Section: Discussionmentioning
confidence: 99%
“…Este fato pode estar relacionado com a presença maciça ainda nesta região do uso dos equídeos como meio de transporte e trabalho, aliado a falhas de manejo sanitário, o que torna os animais mais propensos ao contágio. Vários estudos vêm sendo desenvolvidos no Brasil para identificação dos casos, surtos e estudo da prevalência da doença (Machado et al, 2013;Chaves et al, 2015;Chaves et al, 2016). Devido a gravidade da afecção para a saúde humana e animal, medidas preventivas eficazes devem ser tomadas para conter o avanço da doença no Brasil.…”
Section: Fonte: Autoresunclassified